Determination of the Frequency of Microbial Agents and Drug Susceptibility Pattern of the Neonatal Sepsis in the Neonatal Intensive Care Unit at Alzahra Hospital, Tabriz, Iran - Mohammad Bagher Hosseini; Shahram Abdoli Oskouei; Fariba Heidari; Amin Sadat Sharif; Zakeiye Salimi; Seyed Amir Abbas Sharif (Mashhad University of Medical Sciences, 2019)
Background: Neonatal sepsis is one of the most important causes of infant mortality in developing countries. The causative organisms for sepsis are various in different regions across the world. The aim of this study was to determine the frequency of microbial agents and drug resistance pattern of the neonatal sepsis in newborns admitted to the neonatal intensive care unit (NICU) at Alzahra Hospital Tabriz, Iran. Methods: This descriptive cross-sectional study was carried out from December 2016 to January 2018 in the NICU at Alzahra Hospital Tabriz, Iran. The medical records of all neonates admitted to the NICU were investigated using the convenience sampling method. The data were collected using a two-part demographic form. Subsequently, the data were analyzed in SPSS software (version 22.0). Results: Out of 174 positive blood culture, 52.4% (n=92) and 46.6% (n=82) of Gram-negative (G) and Gram-positive (G) bacteria accounted for the cause of sepsis, respectively. The most common cause of early- and late-onset sepsis was Coagulase-Negative Staphylococci (CoNS), and the most common G-negative and G-positive bacteria were Acinetobacter and CoNS, respectively. The G-positive bacteria showed the most antibiotic susceptibility to Vancomycin (81.45%), Ampicillin (52.15%), and Imipenem (47.32%). On the other hand, the highest drug susceptibility in G-negative bacteria was related to antibiotics, such as Amikacin (73.64%), Imipenem (56.36%), and Ciprofloxacin (52.44%). Moreover, the most antibiotic resistance was associated with Oxacillin (100%), Tetracycline (100%), and Ciprofloxacin (44.4%). Conclusion: The CoNS is the main cause of early- and late-onset sepsis among the neonates admitted to the NICU at Alzahra Hospital, Tabriz, Iran. G-positive and G-negative as causative agents of sepsis showed the highest susceptibility to Vancomycin and Amikacin, respectively.